Pengukuran kinerja green supply chain management berdasarkan green scor Menggunakan Metode OMAX Pada CV. Adila Grup - Muliadi, Muliadi; Rasyid, Abdul; Arafat, Muhammad Yasser (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
CV. Adila Group is an industry engaged in the export and processing of seafood products. In carrying out its supply chain management activities and business operations, the company has not yet conducted performance measurements nor established appropriate indicators to evaluate the performance of its supply chain management. Based on this, the purpose of this research is to identify the key performance indicators (KPIs) that align with the company's needs, assess the performance level of Green Supply Chain Management (GSCM), and determine how to optimize performance in each supply chain activity. The research methods used include the Green Supply Chain Operations Reference (GSCOR), Analytical Hierarchy Process (AHP), Objective Matrix (OMAX), and Traffic Light System. The performance measurement results for the supply chain at CV. Adila Group fall into the yellow category, with a score of 3.7683 across all performance indicators, indicating that improvements are needed.